The discrepancy between macro culture and individual, lived psychology: An ethnographic example of Chinese moral behavior. (September 2017) - Ratner, Carl
This paper seeks to explain the fact that particular cultural structures, artifacts, policies, and values often do not generate corresponding individual behavior/psychology that they are expected to produce. This discrepancy is troubling to the science of cultural psychology/sociocultural activity theory that seeks to understand the cultural organization of psychology; and it it is troubling to policy makers who strive to organize behavior (religious tolerance, diligent work habits, educational learning) through cultural structures and policies. I discuss two explanations for this discrepancy. One is that individual processes contradict cultural influences on psychology. The other explanation is that culture is multifaceted, and cultural factors other than an expected one, are influential in organizing a psychology. I illustrate the second explanation with a case study of moral behavior among Chinese elementary students. These youngsters disobeyed moral teaching in school because they were more influenced by outside influences, ranging from Chinese traditional relations called Guanxi, to modern commercial, privatizing practices. This paper uses individual variations and contradictions in cultural psychology to refine the epistemology and ontology of cultural theory.